Chaplin - Attenborough, Richard; Downey Jr., Robert, 1965-; Geraldine Chaplin; Paul Rhys; John Thaw; Moira Kelly; Anthony Hopkins; Dan Aykroyd; Marisa Tomei; Penelope Ann Miller; Kevin Kline; Maria Pitillo; et al. (UK Carolco Pictures, 1992)
The biography of Charlie Chaplin, filmmaker extraordinaire. From his formitive years in England to his highest successes in America, Charlie's life, work, and loves are followed. While his screen characters were extremely hilarious, the man behind "The Little Tramp" was constantly haunted by a sense of loss.
Languages : English, Turkish Subtitles : English, Turkish
Keywords: Drama; Biography